2019
DOI: 10.1111/dgd.12596
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion of hepatic progenitor cells and differentiation into hepatocyte‐like cells

Abstract: Hepatic progenitor cells (HPCs) in adult liver are promising for treatment of liver diseases. A biliary‐derived HPC population in adult mice has been characterized by co‐expression of stem cell marker Sry (sex determining region Y)‐box 9 (SOX9) and biliary marker cytokeratin 7 (CK7). However, isolation of these HPCs in adult healthy liver without any selection procedures remains a big challenge in this field. Here, by establishing a simple and efficient method to isolate and expand the CK7+SOX9+ HPCs in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Thus, transplanting LPCs seems to be a more reasonable option. The methods available currently for the purification of LPCs are mostly based on fluorescence-activated cell sorting (FACS) via cell labeling with specific antibodies ( Liu et al., 2019b ; Suzuki et al., 2008 ); however, for clinical application, the safety of antibody-conjugated cell transplantation is also of concern. Therefore, the generation of abundant and clinically available LPCs is a new challenge, and more feasible methods should be developed to attain this goal.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, transplanting LPCs seems to be a more reasonable option. The methods available currently for the purification of LPCs are mostly based on fluorescence-activated cell sorting (FACS) via cell labeling with specific antibodies ( Liu et al., 2019b ; Suzuki et al., 2008 ); however, for clinical application, the safety of antibody-conjugated cell transplantation is also of concern. Therefore, the generation of abundant and clinically available LPCs is a new challenge, and more feasible methods should be developed to attain this goal.…”
Section: Introductionmentioning
confidence: 99%
“…6 weeks of oral DEN treatment showed the obvious HPC activation (Additional file 2 : Fig. S3), HPCs were labeled with an antibody against CK7 [ 23 ], and in our previous studies, we found that the activation and malignant transformation of HPCs promote hepatocarcinogenesis and HCC recurrence [ 9 12 ]. Thus, the rats were intrasplenically administered with 40 µg of apoLTC-MPs, apoHep-MPs, apoHPC-MPs or saline after 6 weeks of oral DEN treatment.…”
Section: Resultsmentioning
confidence: 99%
“…4 C, D). To corroborate these observations, we also evaluated the expression of the HPC marker SOX9 and CK7 in liver sections by IHC [ 23 , 24 ]. ApoLTC-MPs and the control group showed intense and diffuse positive SOX9 and CK7 staining, while apoHep-MPs caused a small decrease in the SOX9 and CK7 signal and apoHPC-MPs caused a significant decrease in SOX9 and CK7 staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These cells can be lineage-restricted into hepatocytes under different condition, which indicates that they are safe for use in transplantation in vivo (Cardinale et al, 2011;Turner et al, 2011). However, the extraction and separation of HpSCs or hepatoblasts presents a challenge due to the scant numbers of HpSCs (0.5-2.5% of liver parenchyma of all donor ages) and hepatoblasts (<0.01% in adult livers) (Turner et al, 2011;Liu et al, 2019). Although it is possible to obtain proliferative hepatoblasts by transferring both stem maintaining genes and liver specific genes, the final differentiation efficiency seems to be dissatisfactory (only 56.7%) (Yu et al, 2013;.…”
Section: Hepatic Stem/progenitor Cellsmentioning
confidence: 99%